Fatores críticos para a implementação do Escritório de Projetos: um estudo de caso - Abe, César Kendi; de Carvalho, Marly Monteiro (Revista Gestão da Produção Operações e Sistemas, 2006)
The aggressive competition of the globalized market drives the companies to the search of new ways to overcomehardships and assure their survival. In this scenario, the companies are required to present a number of abilitiesin order to become or remain as a potential player, which are constantly being put to the proof in these moreand more selective scenarios.Especially in the service sector, in which is not always possible to objectively measure the results, and specialfocus is on the processes improvement, which will result in the quality of the deliverables. In this sense, topicsregarding project management have been extensively explored, and this management is strongly connected withthe process control. Many organizations and professionals have been currently attempting to become familiarwith these practices, aiming, through them, at the obtainment of competitive advantages. Thus, this paper aimsat presenting the concepts of project management in general, specifically PMO (Project Management Office)and finally present a case study of a company that foresaw the PMO as an improving tool for its projectmanagement.Keywords: Project management; Project management office; Structures.